Targeted delivery of YSA-functionalized and non-functionalized polymeric nanoparticles to injured pulmonary vasculature. (12th November 2018) - Patil, Madhoosudan A.; Upadhyay, Arun K.; Hernandez-Lagunas, Laura; Good, Ryan; Carpenter, Todd C.; Sucharov, Carmen C.; Nozik-Grayck, Eva; Kompella, Uday B.
Abstract: Ephrin type-A receptor 2 (EphA2) is a transmembrane receptor which is upregulated in injured lungs, including those treated with bleomycin. YSA peptide (YSAYPDSVPMMS), a mimic of ephrin ligands, binds to EphA2 receptors on cell surface with high affinity. In this study, we assessed the ability of YSA-functionalized and non-functionalized poly (dl -lactide-co-glycolide) (PLGA) nanoparticles to enhance delivery to bleomycin treated cultured vascular endothelial cells and, in a bleomycin induced lung injury mouse model. Nanoparticles were loaded with a lipophilic fluorescent dye. Human umbilical vein endothelial cells (HUVEC) with or without 2-day bleomycin pretreatment (25 µg/ml) and adult mice with or without intratracheal instillation of bleomycin (0.1 U) were dosed with nanoparticles. Mice received nanoparticles via tail vein injection 4 days after bleomycin treatment. Three days after nanoparticle injection, tissues (lung, heart, kidney, spleen, liver, brain, eyes and whole blood) were harvested and quantified for fluorescence using IVIS imaging. Mean particle uptake increased with time and concentration for both types of particles in HUVEC, with the uptake being higher for YSA-functionalized nanoparticles. Bleomycin treatment increased the 3-h uptake of both types of nanoparticles in HUVEC by about two-fold, with the YSA-functionalized nanoparticle uptake being 1.66-fold compared to non-functionalized nanoparticles ( p < .05). In mice, bleomycin injury resulted in 2.3- and 4.7-fold increase in the lung levels of non-functionalized and YSA-functionalized nanoparticles ( p < .05), respectively, although the differences between the two particle types were not significant. In conclusion, PLGA nanoparticle delivery to cultured vascular endothelial cells and mouse lungs in vivo is higher following bleomycin treatment, with the delivery tending to be higher for YSA functionalized nanoparticles.